2021
DOI: 10.1186/s12870-021-03034-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of aquaporin family in Canavalia rosea and their roles in the adaptation to saline-alkaline soils and drought stress

Abstract: Background Canavalia rosea (Sw.) DC. (bay bean) is an extremophile halophyte that is widely distributed in coastal areas of the tropics and subtropics. Seawater and drought tolerance in this species may be facilitated by aquaporins (AQPs), channel proteins that transport water and small molecules across cell membranes and thereby maintain cellular water homeostasis in the face of abiotic stress. In C. rosea, AQP diversity, protein features, and their biological functions are still largely unkno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Subsequently, the expression of seven RsPIP genes was upregulated under salt exposure, indicating that they might play a crucial role in the response to salt stress. Similar results were also observed in soybean (Zhou et al, 2014), Arabidopsis (Feng et al, 2018), and Canavalia rosea (Lin et al, 2021). The distribution of RsAQP in linkage groups showed tandem duplicated pairs, such as RsPIP2-1, RsPIP2-2, RsPIP2-3, and RsPIP2-4, on the R6 chromosome, which might have been caused by gene duplication during evolution.…”
Section: Characterization Of Aqp Gene Family Members In Radishsupporting
confidence: 79%
“…Subsequently, the expression of seven RsPIP genes was upregulated under salt exposure, indicating that they might play a crucial role in the response to salt stress. Similar results were also observed in soybean (Zhou et al, 2014), Arabidopsis (Feng et al, 2018), and Canavalia rosea (Lin et al, 2021). The distribution of RsAQP in linkage groups showed tandem duplicated pairs, such as RsPIP2-1, RsPIP2-2, RsPIP2-3, and RsPIP2-4, on the R6 chromosome, which might have been caused by gene duplication during evolution.…”
Section: Characterization Of Aqp Gene Family Members In Radishsupporting
confidence: 79%
“…As these genes have not been implicated in alkalinity tolerance, we selected four genes from the 10.18 QTL region for expression analysis under alkaline stress ( Figure 5 ). Several studies showed that overexpression of aquaporin genes has a negative impact on salt and alkaline stress [ 43 , 44 ]. These findings further corroborate the downregulation of LOC_Os10g34000 in the tolerant cultivar used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the degeneracy of the code, sites within codons were defined as synonymous substitutions (Ks) when they did not result in an amino acid change, and as a non-synonymous substitutions (Ka) when they did ( Harouaka et al., 2016 ). Generally, Ka/Ks >1 indicates positive selection, Ka/Ks =1 indicates neutral selection, and Ka/Ks <1 indicates purified selection ( Lin et al., 2021 ). Based on the Ka/Ks ratio, all PsbHLH pairs were subjected to purifying selection.…”
Section: Discussionmentioning
confidence: 99%